2012
DOI: 10.1074/jbc.m111.299149
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into Recognition of Methylated Histone Tails by Retinoblastoma-binding Protein 1

Abstract: Background: Retinoblastoma-binding protein 1 (RBBP1), a tumor suppressor, is involved in epigenetic regulation in cancer. Results: The chromobarrel domain of RBBP1 binds methylated histone tails, whereas Tudor and PWWP domains do not. Conclusion:The chromobarrel domain of RBBP1 is responsible for epigenetic regulation. Significance: Our research provides a structural basis to understand the mechanism of RBBP1-mediated epigenetic regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 37 publications
6
42
0
Order By: Relevance
“…RBBP1 and RBBP1L1 regulate epigenetic marks, such as methylation of lysines in histones H3 and H4, which are observed in leukemia and Prader-Willi/Angelman syndromes (2,11). The epigenetic regulation function of RBBP1 was proposed to be mediated by its three Royal Family domains (2,11,12), including the chromobarrel domain, Tudor domain, and Pro-Trp-Trp-Pro (PWWP) domain, but our previous study indicated that of these three domains, only the chromobarrel domain can bind with histone tails and is responsible for the epigenetic regulation function (13). RBBP1 and RBBP1L1 are also known as ARID4A and ARID4B, respectively, because they each contain an ATrich interaction domain (ARID) and bind to DNA nonspecifically, presumably through this domain (14).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…RBBP1 and RBBP1L1 regulate epigenetic marks, such as methylation of lysines in histones H3 and H4, which are observed in leukemia and Prader-Willi/Angelman syndromes (2,11). The epigenetic regulation function of RBBP1 was proposed to be mediated by its three Royal Family domains (2,11,12), including the chromobarrel domain, Tudor domain, and Pro-Trp-Trp-Pro (PWWP) domain, but our previous study indicated that of these three domains, only the chromobarrel domain can bind with histone tails and is responsible for the epigenetic regulation function (13). RBBP1 and RBBP1L1 are also known as ARID4A and ARID4B, respectively, because they each contain an ATrich interaction domain (ARID) and bind to DNA nonspecifically, presumably through this domain (14).…”
mentioning
confidence: 99%
“…Our previous studies indicated that the RBBP1 Tudor domain has low sequence homology to other known Tudor domains and cannot recognize epigenetic marks (13). In order to further understand the function of the RBBP1 Tudor domain, we have now determined its solution structure, which shows an interdigitated double Tudor fold similar to the epigenetic mark reader JMJD2A.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1). However, some PWWP domains contain a truncated version of the aromatic cage, lacking one of the three aromatic residues, and thus are unable to bind histone methyl-lysines (Gong et al 2012).…”
Section: Structural Features Of Pwwp Domainsmentioning
confidence: 99%